Integrating Active Disturbance Rejection Control and Input Shaping for Enhanced Vibration Control of Warehouse Single Mast Stacker Crane - Thi Ly Tong; Duy Canh Nguyen; Minh Duc Duong (Journal of Applied Science and Engineering)
Warehouse single mast stacker cranes, which can reach heights of 80 meters, are becoming increasingly popular in the e-commerce sector as automated storage solutions due to their many benefits. Because stacker cranes are high and expected to move rapidly, the vibrations are inevitable. Therefore, it is essential to reduce unwanted vibrations to protect the structure and ensure precise positioning. To conduct this study, a system of partial differential equations has been developed to model the single mast stacker crane. The analysis of this model has led to a control solution that integrates Active Disturbance Rejecting Control (ADRC) with input shaping (IS) methods to provide precise positioning and vibration suppression. As demonstrated by simulation, the system is stable using the proposed control algorithm, the driving unit position is controlled precisely, and vibrations are nearly eliminated. In addition, an experimental prototype model has been developed to test the feasibility in practice, and the results indicate that the proposed controller can work effectively and be evaluated as a potential industrial solution.